Market potential study for standing cabin concept for domestic low-cost commercial airlines in Malaysia - Romli, Fairuz Izzuddin; Dasuki, Norhafizah; Harmin, Mohammad Yazdi (IOP Publishing, 2015)
An affordable air transportation has become the operational aim of many airlines these days. This is to cater the growing air travel demands from people of different social and economic status. One of the revolutionary proposals to reduce the operational costs, hence the flight ticket price, is by introducing the so-called standing cabin concept. This concept involves transporting passengers during the entire flight in their standing position with a proper support of a vertical seat. As can be expected with many new inventions, despite its clear advantages, the concept has been met with mixed reactions from the public. This study intends to establish whether the standing cabin concept has a market potential to be implemented for domestic flights in Malaysia. The public perception is determined from collected data through a survey done at two major local low-cost airport terminals. It can be concluded from the results that the concept has a good market potential for application on flights with duration of less than two hours.